A331 QUALITY GAPS IN THE MANAGEMENT OF PATIENTS WITH ACUTE PANCREATITIS. (1st March 2018) - Ahmed, O; Teshima, C W; Akram, H; Mosko, J
Abstract: Background: Acute pancreatitis is the most common gastrointestinal (GI) cause for hospitalization and is associated with high morbidity and mortality. Multiple clinical guidelines outline best practices for the management of these patients. However, recent studies suggest that adherence to such guidelines is poor. Aims: In this study, we aim to audit current practice to identify potential targets for quality improvement initiatives. Methods: A retrospective chart review of all patients admitted directly to St. Michael's Hospital (a tertiary-care hospital) from the Emergency Department with a diagnosis of acute pancreatitis between July 1, 2016 and December 31, 2016 was performed. Complex patients transferred from another hospital to the ICU or GI ward were excluded. Patients were identified using ICD-10 discharge codes. Potential quality indicators were extracted from the recent AGA, ACG and recently published Canadian guidelines on the management of acute pancreatitis. Individual charts were reviewed and the following data was extracted: laboratory values, imaging results, dates of admission and, discharge, interventions/procedures performed, antibiotic use and nutrition. The data was were then used to determine baseline characteristics and adherence to guidelines. Results: A total of 55 patients were included in the study. The mean age was 50 (range 16 to 92) years and 31 (56%) were male. The most common cause of acute pancreatitis was idiopathic (36%), followed by alcohol (22%) and gallstones (20%). The average Charlson co-morbidity index was 2.4 (+/- 2.6). The average length of stay was 5.8 (range 1 to 46) days. 3 patients required ICU admission. Ultrasound was performed within 48 hours of admission in 28 (51%) patients, while 23 (42%) patients had a CT scan during their admission. The most common reason for CT was for diagnostic evaluation (52%), followed by investigation for underlying etiology (30%). 25% of patients did not obtain any imaging during their admission. 2 (4%) patients did not receive nutrition within 48 hours, with the average time to nutrition being 1 day. Antibiotic prophylaxis was started in 4 (7%) patients. The average fluid resuscitation rate was 113 (+/- 64) mL/hour. No patients had appropriate lab values drawn to calculate Apache or other severity index scores. Only 3 patients had CRP measured. For patients with biliary pancreatitis, 5/13 required ERCP during their admission (all for ongoing biliary obstruction), and only 36% underwent cholecystectomy within the same admission. Conclusions: The management of patients presenting with acute pancreatitis remains quite variable, with the most common deficiencies relating to imaging for potential etiologies, risk stratification, under resuscitation with intravenous fluids and delay to cholecystectomy. Funding Agencies: None